The effect of a researcher-made educational booklet on the correct French pronunciation of Iranian students - Shahin Norouzi, Yasamin Mohammadi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main purpose of this article is to investigate the effect of a researcher-made educational booklet on the correct pronunciation of 100 difficult words selected among French language undergraduate students studying in Iranian universities. This research is in the category of developmental research in terms of purpose and is considered as experimental studies in terms of data collection method. In this study, the experimental design of pre-test post-test with control group with follow-up was used. The results showed that the intervention in the pre-test, post-test and follow-up stages had an effect on the correct pronunciation variable of one hundred words in both groups and the difference was significant and therefore the researcher-made textbook on the correct pronunciation of one hundred difficult words selected among French undergraduate students. It has a positive effect on studying in Iranian universities. Therefore, the hypothesis of the present study was confirmed.